2010
DOI: 10.1593/neo.10166
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tumor and Microenvironment Secretomes in Plasma and in Platelets during Prostate Cancer Growth in a Xenograft Model

Abstract: To survive and metastasize, tumors interact with surrounding tissues by secreting growth factors and cytokines. In return, surrounding host tissues respond by changing their secretome. Numerous factors theoretically function as therapeutic targets or biomarkers of cancer growth and metastatic risk. However, it is unclear if these factors are tumor-derived or actually represent the host defense. To analyze the concentrations of tumor- and microenvironment-derived factors associated with neoplastic growth, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Interest in platelets and their ability to interact with intravascular components have enticed several groups to pursue the use of platelets as a protein source for cancer biomarkers and investigating their function in disease. [18][19][20][21][22] Several platelet proteins were identified as potential cancer biomarkers, including PF4 23 and thrombospondin-1. 24 Interestingly, thrombospondin-1 was shown to be a negative regulator of angiogenesis and affects plateletmediated recruitment of bone marrow-derived cells to sites of tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in platelets and their ability to interact with intravascular components have enticed several groups to pursue the use of platelets as a protein source for cancer biomarkers and investigating their function in disease. [18][19][20][21][22] Several platelet proteins were identified as potential cancer biomarkers, including PF4 23 and thrombospondin-1. 24 Interestingly, thrombospondin-1 was shown to be a negative regulator of angiogenesis and affects plateletmediated recruitment of bone marrow-derived cells to sites of tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Kerr and colleagues showed that many tumor-secreted proteins are taken up and stored in platelets and specifically released at the metastatic sites. 13 However, while the ability of cancer cells to aggregate and cluster platelets around the tumor is supported by a large body of experimental and clinical data, 32,45,46 the role of cancer cells in promoting platelet secretion of procarcinogenic and thrombotic factors is poorly understood. In the present study, we show that highly metastatic colorectal cancer cells (Caco-2) and a prostate carcinoma cell line (PC3M-luc) stimulate the release of plateletdense granule contents in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, platelet a-granules contain large reservoirs of cytokines and growth factors, including transforming growth factor b (TGF-b) and vascular endothelial growth factor (VEGF), 10,11 which are selectively released upon platelet activation. 12,13 Consistent with a role of platelet secretion in tumor metastasis, TGF-b derived from platelet a-granules has been shown to profoundly impact tumor metastasis and survival by enhancing an epithelial mesenchymal-like transition and suppressing tumor cell natural killer-mediated lysis, respectively. 2,3 Moreover, platelet secretion in a tumorigenic microenvironment seems to differ materially from wound-induced platelet secretion.…”
Section: Introductionmentioning
confidence: 85%
“…Analyses of the complete set of secreted proteins -otherwise known as the "secretome" -have been reported in various organisms, cell types, and pathologies, and are quickly gaining popularity [6,7]. Not surprisingly, several studies have focused on analyses of cancer-or metastasis-specific changes in secretome profiles [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, none of the studies to date has focused on secretomes relevant to the bone metastasis phenotype.…”
Section: Introductionmentioning
confidence: 99%